Ventricular Fibrillation-Induced Cardiac Arrest Results in Regional Cardiac Injury Preferentially in Left Anterior Descending Coronary Artery Territory in Piglet Model. (2nd November 2016) - Venkata, Giridhar Kaliki; Forder, John R.; Clark, Dan; Shih, Andre; Udassi, Sharda; Badugu, Srinivasarao; Lamb, Melissa A.; Porvasnik, Stacy L.; Shih, Renata S.; Colon-Lopez, Dalia; Zaritsky, Arno L.; Haque, Ikram U.; et al.
Abstract : Objective . Decreased cardiac function after resuscitation from cardiac arrest (CA) results from global ischemia of the myocardium. In the evolution of postarrest myocardial dysfunction, preferential involvement of any coronary arterial territory is not known. We hypothesized that there is no preferential involvement of any coronary artery during electrical induced ventricular fibrillation (VF) in piglet model. Design . Prospective, randomized controlled study. Methods . 12 piglets were randomized to baseline and electrical induced VF. After 5 min, the animals were resuscitated according to AHA PALS guidelines. After return of spontaneous circulation (ROSC), animals were observed for an additional 4 hours prior to cardiac MRI. Data (mean ± SD) was analyzed using unpaired t -test; p value ≤ 0.05 was considered statistically significant. Results . Segmental wall motion (mm; baseline versus postarrest group) in segment 7 (left anterior descending (LAD)) was 4.68 ± 0.54 versus 3.31 ± 0.64, p = 0.0026 . In segment 13, it was 3.82 ± 0.96 versus 2.58 ± 0.82, p = 0.02 . In segment 14, it was 2.42 ± 0.44 versus 1.29 ± 0.99, p = 0.028 . Conclusion . Postarrest myocardial dysfunction resulted in segmental wall motion defects in the LAD territory. There were no perfusion defects in the involved segments.